Identification of ageing state clusters of reclaimed asphalt binders using principal component analysis (PCA) and hierarchical cluster analysis (HCA) based on chemo-rheological parameters. (30th May 2020) - Margaritis, Alexandros; Soenen, Hilde; Fransen, Erik; Pipintakos, Georgios; Jacobs, Geert; Blom, Johan; Van den bergh, Wim
Graphical abstract: Highlights: A large selection of RA binders was chemically and rheologically tested. Ageing states can be distinguished based on HCA and PCA analyses. RA binders showing similar basic properties differ in terms of their ageing state. Abstract: Nowadays, Reclaimed Asphalt (RA) is widely used in pavement applications as part of new asphalt mixtures. To design high-quality asphalt mixes, the RA material and especially the RA binder must be systematically characterised with the purpose to explore its ageing state, especially when RA is added in high rates (above 20%). In this research, chemical (SARA and FTIR ageing indexes) and rheological properties (master curve parameters, Glower-Rowe parameter and ΔΤc ) of a large selection of RA binders (19 samples) were determined to reveal their ageing level. The results of this experimental validation were further analysed statistically to discover clusters of similar chemorheological properties, reflecting in this way their ageing state. The exploratory techniques PCA and HCA were able to detect five clusters of RA binders with different ageing states. The five clusters clearly distinguish the RA binders in groups with statistically different properties, assessed using one-way ANOVA. The method proposed here is a potential tool to "fingerprint" RA binders with similar ageing states, particularly for decision-making strategies, to optimise the use and treatment of RA.